GENRE FEATURES OF THE WORK “AMONG THE RUINS - Manzura Akhronqulovna Jo‘rayeva (Bright Mind Publishing, 2025)
This article examines the travelogue genre and its characteristics. It explores the genre's characteristics in Abdulhamid Sulaymon ugli Cholpon's "Among the Ruins." It provides a scientific justification for the types and directions of the travelogue genre. Specific facts, landscapes, and fictional images in the work are analyzed, and the author's concept is explored.